2021
DOI: 10.1177/11782218211053360
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives on Barriers and Facilitators to Implementing e-Health Technology in Substance Use Disorder (SUD) Treatment Facilities

Abstract: Background: Substance use disorders (SUDs) in the United States cause many preventable deaths each year. Finding effective ways to manage SUDs is vital to improving outcomes for individuals seeking treatment. This has increased interest in using e-health technologies in behavioral healthcare settings. This research is part of a larger study evaluating the efficacy of the NIATx coaching intervention for implementing RISE Iowa, an e-health patient recovery app, in SUD treatment organizations and seeks to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Treatment providers then offered RISE Iowa to patients they deemed may benefit from RISE as a supplement to their ongoing SUD treatment. Initial data suggest that some providers targeted patients who they thought would be more likely to use it, like younger patients or those with internet access, whereas other providers reported offering the app to most or all patients 21 . Providers also had discretion in the types of introductory training they provided to their patients about the app.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment providers then offered RISE Iowa to patients they deemed may benefit from RISE as a supplement to their ongoing SUD treatment. Initial data suggest that some providers targeted patients who they thought would be more likely to use it, like younger patients or those with internet access, whereas other providers reported offering the app to most or all patients 21 . Providers also had discretion in the types of introductory training they provided to their patients about the app.…”
Section: Methodsmentioning
confidence: 99%
“…Providers also had discretion in the types of introductory training they provided to their patients about the app. For example, providers reported introducing the app in both group and individual treatment settings and often provided a brief overview of the app and its features to patients 21 . Additional funding, through a Helping to End Addiction Long-term supplement, in addition to the parent implementation trial, was received to examine the impact of COVID-19 on patients of participating organizations who had signed up for an A-CHESS account about their experiences with SUD treatment during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a study that examined SUD treatment access pre-ACA (2009–2013) and post-ACA (2015–2019) did not find a significant increase in treatment entry among adults who have a SUD with a lower socioeconomic status [ 5 ]. Instead, the authors found that while some barriers to accessing treatment increased during the analytical period (e.g., lack of knowledge of available services, perceived stigma, and difficulties accessing appropriate treatment options), there was no significant reduction in insurance-related treatment barriers, highlighting the importance of considering multiple factors to increase SUD treatment access [ 4 , 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%